2005
DOI: 10.1111/j.1365-2729.2005.00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a mobile learning organiser for university students

Abstract: This paper describes a 10-month trial of a mobile learning organiser, developed for use by university students. Implemented on a wireless-enabled Pocket PC hand-held computer, the organiser makes use of existing mobile applications as well as tools designed specifically for students to manage their learning. The trial set out to identify the most-used tools for such a learning device and their patterns and problems of usage. The primary uses of the organiser were communication, time-management and access to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
2
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(77 citation statements)
references
References 4 publications
0
67
2
8
Order By: Relevance
“…Several studies (Corlett et al, 2005;Muthaiyah, 2004;Rekkedal and Dye, 2007;Seppala et al, 2002) noted that mobile devices have some limitations including: Memory size, battery life, high line cost and small screen. These limitations can hinder using mobile technology widely in learning.…”
Section: Limitations Of M-learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies (Corlett et al, 2005;Muthaiyah, 2004;Rekkedal and Dye, 2007;Seppala et al, 2002) noted that mobile devices have some limitations including: Memory size, battery life, high line cost and small screen. These limitations can hinder using mobile technology widely in learning.…”
Section: Limitations Of M-learningmentioning
confidence: 99%
“…These limitations can hinder using mobile technology widely in learning. Nevertheless, Corlett et al (2005) gave directions to extend the wireless network across the campus and to redesign software as well as hardware for m-learning purposes. Hence, university environment will be adequate to utilize the latest technology innovation without delay (Seppala et al, 2002).…”
Section: Limitations Of M-learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Research from a study involving loaned personal digital assistants (PDAs) found that some of the students did not appropriate the device due to that fact the devices were loaned and not given. The students were reluctant to invest time and money in personalizing and extending the PDAs if they were unable to keep the devices at the project's conclusion (Corlett et al, 2005).…”
Section: Attachmentmentioning
confidence: 99%
“…Los estudiantes señalan la flexibilidad que aporta un dispositivo móvil para ayudar en su proceso de aprendizaje. Corlett et al (2005) …”
Section: Aprendizaje Móvil (Mobile Learning)unclassified